2007
DOI: 10.1016/j.freeradbiomed.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of pro-oxidants and antioxidants in the anti-inflammatory and apoptotic effects of curcumin (diferuloylmethane)

Abstract: Extensive research within last half a century has indicated that curcumin (diferuloylmethane), a yellow pigment in curry powder, exhibits antioxidant, anti-inflammatory and proapoptotic activities. Whether anti-inflammatory and proapoptotic activities assigned to curcumin, are mediated through its antioxidant mechanism was investigated. We found that TNF-mediated NF-κB activation was inhibited by curcumin; and glutathione reversed the inhibition. Similarly, suppression of TNFinduced AKT activation by curcumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(189 citation statements)
references
References 63 publications
6
175
1
7
Order By: Relevance
“…40,[44][45][46][47][48] Experimental studies have demonstrated that, although low concentrations of curcumin induce antioxidant effects, higher concentrations of this compound increase the cellular levels of ROS. 4,9,23,28,[49][50][51][52][53] The presence of 2 a,b-unsaturated ketones in the chemical structure of curcumin may also mediate some of its negative properties. These chemical groups are known to react covalently with exposed thiol groups of cysteine residues of proteins through a reaction termed Michael addition.…”
Section: Dear Editormentioning
confidence: 99%
“…40,[44][45][46][47][48] Experimental studies have demonstrated that, although low concentrations of curcumin induce antioxidant effects, higher concentrations of this compound increase the cellular levels of ROS. 4,9,23,28,[49][50][51][52][53] The presence of 2 a,b-unsaturated ketones in the chemical structure of curcumin may also mediate some of its negative properties. These chemical groups are known to react covalently with exposed thiol groups of cysteine residues of proteins through a reaction termed Michael addition.…”
Section: Dear Editormentioning
confidence: 99%
“…For several decades curcumin has been widely used as a food coloring ingredient for its yellowish color. In the last 10 years, several in vitro and in vivo studies have reported that curcumin possesses significant pharmacological actions, such as anti-tumor effects, anti-inflammatory effects and induction of apoptosis of cancer cells (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The study further concludes that relaxation of porcine arterial rings by curcumin is mediated through NO, cGMP and β-adrenoreceptors (Xu et al, 2007). Curcumin has been shown to affect number of molecular targets including transcription factor p53 and cyclin-dependent kinase inhibitor (CDKI) p21 via its role as a pro-and antioxidant (Sandur et al, 2007). Our studies indicate that combination of curcumin + NOC-18 increased the accumulation of transcription factor p53 with concomitant increase in the protein levels of CDKI p21 and cardiac specific protein MLC2 and troponin I compared to either of the two agents alone.…”
Section: Tablementioning
confidence: 75%